2013
DOI: 10.1021/es4033265
|View full text |Cite
|
Sign up to set email alerts
|

Dark Formation of Hydroxyl Radical in Arctic Soil and Surface Waters

Abstract: Hydroxyl radical (•OH) is a highly reactive and unselective oxidant in atmospheric and aquatic systems. Current understanding limits the role of DOM-produced •OH as an oxidant in carbon cycling mainly to sunlit environments where •OH is produced photochemically, but a recent laboratory study proposed a sunlight-independent pathway in which •OH forms during oxidation of reduced aquatic dissolved organic matter (DOM) and iron. Here we demonstrate this non-photochemical pathway for •OH formation in natural aquati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
196
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(207 citation statements)
references
References 49 publications
9
196
2
Order By: Relevance
“…elevated [COH] levels, which could be important in the transformation of dissolved compounds. [134,135] As far as the H 2 O 2 -independent formation of COH by irradiated CDOM is concerned, the detailed pathways are still to be elucidated. For instance, while some excited triplet states are able to oxidize water and/or OH À to COH, [136,137] this is not a general feature of triplet-state reactivity.…”
Section: Hydroxyl Radicals (Coh)mentioning
confidence: 99%
“…elevated [COH] levels, which could be important in the transformation of dissolved compounds. [134,135] As far as the H 2 O 2 -independent formation of COH by irradiated CDOM is concerned, the detailed pathways are still to be elucidated. For instance, while some excited triplet states are able to oxidize water and/or OH À to COH, [136,137] this is not a general feature of triplet-state reactivity.…”
Section: Hydroxyl Radicals (Coh)mentioning
confidence: 99%
“…These products were not observed in this study; the ketone and alcohol analogs observed here were less polar than the parent PhAC. Recent reports of dark hydroxyl radical formation in arctic soils (Page et al, 2013) indicate the possibility that hydroxyl radical mediated transformation could contribute to soil transformation as it does with DOM-mediated phototransformation.…”
Section: Correlation Between Transformation Products Formed In Soil Amentioning
confidence: 99%
“…Note that rates of superoxide production normalized to the proportion of metabolically active cells is detected to vary between 0.02  0.02 amol cell −1 hour −1 (mean ± standard error) and 19.4  5.2 amol cell −1 hour −1 [1]. Such biological formation of H 2 O 2 subsequently could be link with dark formation of hydroxyl radical (HO • ) in Arctic soil and surface waters [13,14].…”
Section: Canadian Chemical Transactionsmentioning
confidence: 96%